Men and women : partners at work - Simons, George F. (Crisp Pub. Menlo ParkUS, 1990)
Identifies and explores ten tasks which focus on ten person-to-person skills needed by men and women in order to work comfortably with each other. Tasks explored include: accepting gender differences; speaking with respect; collaborating; and, paying attention to each other.